Regulation of Public Finances in Croatia in Light of Financial Constitutionality - Klemenčić, Irena; Lugarić, Tereza Rogić (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
This chapter describes the basic features of financial law and financial regulation in the Republic of Croatia. With the aim of defining financial law in Croatia, the authors provide the setting thereof in the Croatian legal system and address the main areas which it encompasses. The introductory part describes the development of Croatian financial law and sets the boundaries by identifying the areas it includes. Beginning in the early 1990s, marked by the transition to market economy, the introduction of new tax forms as well as the development of tax procedure and tax administration are explained. Simultaneously, budgetary law, social contributions law, law on financing local and regional units, fees law and customs law were created to eventually assume their present form. Starting from the constitutional provisions, this chapter sets all those areas in the framework of financial law regulation and provides basic information for each of them. The descriptions include the concepts and instruments of financial law in Croatia, starting with the budget law of the state and of local self-government, followed by tax and fee law, customs law, and social insurance law. The overview is supplemented by the most important aspects of tax procedure and tax administration. The conclusion reflects on the present state of Croatian financial law, the challenges that influenced its development, and the prospects for the future.KEYWORDS: Financial law, budget, tax, customs, social security contributions, Croatia.